Determinants of Net Returns and Supply Chain Dynamics in Apple Production: Evidence from Balochistan, Pakistan - Zubari Khan; Amjad Ali; Nighat Ara; Mansoor Rasheed; Syed Attaullah Shah (Indus Journal of Social Sciences, 2025)
Current study was conducted in Balochistan (Killa Saifullah and Pishin districts) province with main aims to analyze profitability and supply chain efficiency of apple growers. Primary data of 120 apple growers was analyzed to interpret results of the study by applying linear regression model and descriptive statistics. Results shows that growers’ average net returns per acre in Pishin and Killa Saifullah are Rs. 567,850/- and Rs. 506,750. Selling orchards to pre- contractors in the ripening and blossom stage has lowered net returns by Rs. 53,292/- and Rs. 256,667/-. In inputs picking and packaging materials, transportation and irrigation cost was noted high. Commission agents in local and city market received 4% and 10 % of the overall sale respectively as their services charges. Contractors, local commission agents and transporters are essential participants in the apple supply chain. Regression analysis illustrated positive and significant association for producer age, relevant experience, orchard selling stage choices, marketing channel adopted by producers, irrigation water availability, climatic factors, distance to main road and infrastructure quality with growers’ net returns. The study recommends drip irrigation systems, low interest credits, auction facility in local market, focus on improvement of farmers’ technical abilities for improvement of efficiency, profitability and food security of growers along with all stakeholders in apply supply chain.